Factors Associated With Coverage in Community-directed Treatment With Ivermectin for Onchocerciasis Control in Savanah and Forest Areas in Central African Republic: A Cross-sectional Study - Sylvain Honoré Woromogo; Stéphanie Inesse Garoua-Adjou; Ange Donatien Ngouyombo; Rodrigue Herman Doyama-Woza; Henri Saint Calvaire Diemer; Jean de Dieu Longo (Korean Society for Preventive Medicine, 2024)
Objectives: The aim of this study was to identify factors associated with coverage in community-directed treatment with ivermectin for onchocerciasis control in savannah and forest areas in the Central African Republic. Methods: A cross-sectional study was conducted in 2 districts where onchocerciasis is endemic. We employed a pretested and validated questionnaire that included questions about the socio-demographic characteristics of the respondents and variables relevant to coverage assessment. Multivariate logistic regression analyses were performed to identify the associations between surveyed mass drug administration (MDA) coverage and the variables considered, while accounting for potential confounding factors. A p-value <0.05 was considered statistically significant. Results: At the district level, the MDA program achieved a reach of 87.29% (95% confidence interval [CI], 86.03 to 88.55) in Bossangoa and 61.74% (95% CI, 59.56 to 63.92) in Kémo, compared to the reported rates of 90.02% and 91.70%, respectively. Women in both Bossangoa and Kémo were 1.28 times more likely to have taken ivermectin than men (95% CI, 1.12 to 1.47; p=0.008; 95% CI, 1.09 to 2.00; p=0.041, respectively). The age groups of 5-14, 15-24, and 25-34 were statistically associated with better distribution coverage in both districts. Individuals with knowledge of onchocerciasis were more likely to receive ivermectin compared to those without knowledge, with adjusted odds ratios of 1.41 (95% CI, 1.11 to 2.01; p=0.030) and 3.19 (95% CI, 2.91 to 4.08; p=0.001), respectively. Conclusions: The authors recommend implementing measures to improve MDA coverage in future campaigns. These measures should include allocating sufficient time for MDA activities, providing health education, and mobilising the entire population.